2014
DOI: 10.5761/atcs.oa.13.02282
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia or High Hemoglobin A1C: Which One is More Associated with Morbidity and Mortality after Coronary Artery Bypass Graft Surgery?

Abstract: Propose: Our aim was to determine which criterion-hyperglycemia or high levels of glycosylated hemoglobin (HbA1C) is more associated with increased mortality and morbidity after coronary artery bypass graft (CABG). Methods: Two hundred and sixteen patients who underwent elective CABG were enrolled in this prospective study. In order to compare postoperative outcomes regarding HbA1c and fasting blood sugar (FBS) levels, the patients were divided into two groups based on plasma HbA1c levels >7% or ≤7% and FBS >1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…Hemoglobin A 1c (HbA 1c ) is widely used as a marker of average blood glucose concentrations over the preceding 2 to 3 months and it has advantages over glucose tests [7] . Some evidence indicates that high HbA 1c levels prior to surgery are strongly associated with the severity of adverse events after CABG [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin A 1c (HbA 1c ) is widely used as a marker of average blood glucose concentrations over the preceding 2 to 3 months and it has advantages over glucose tests [7] . Some evidence indicates that high HbA 1c levels prior to surgery are strongly associated with the severity of adverse events after CABG [8] .…”
Section: Introductionmentioning
confidence: 99%
“…19 While elevated HbA1c is common among hospitalized patients, it has not been clearly established that this is predictive of postoperative hyperglycemia in patients undergoing non-cardiac surgery. 19,20 Recent studies of abdominal surgery suggest that elevated HbA1c is associated with major cardiac complications, while hyperglycemia is more likely to be associated with SSI, emphasizing the importance of identifying both of these risk factors. 2,14 If this were indeed the case, widespread HbA1c screening and postoperative glucose testing would each identify different types of high-risk patients to target for intervention strategies.…”
Section: Résumémentioning
confidence: 99%
“…During 120 days of erythrocyte lifespan, the rate of glycosylation of hemoglobin increases in parallel with the blood glucose levels. The HbA1c test measures the rate of glycosylation; therefore, HbA1c provides information about the blood glucose profile belonging to the erythrocyte lifespan, which is past 2-3 months [5,6]. The assessment of HbA1c level should be carried out using certified analytical methods recommended by the National Glycohemoglobin Standardization Program (NGSP), American (ADA) and European (EASD) Diabetes Associations [7].…”
Section: Introductionmentioning
confidence: 99%
“…Considering these high rates, mortality and postoperative complications should have been expected to be very high postoperatively. After the studies on HbA1c, which is reported to strongly predict mortality, publications suggesting that high HbA1c can predict postoperative adverse events but cannot reveal any presumption related to mortality started to become evident in the literature [6,10]. Moreover, it is even controversial whether or not high HbA1c levels are a good biomarker for the development of diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation